Test Suite Generation for Boolean Conditions with Equivalence Class Partitioning - Halle, Sylvain (2022 IEEE/ACM 10th International Conference on Formal Methods in Software Engineering (FormaliSE), 2022)
Boolean test input generation is the process of finding sets of values for variables of a logical expression such that a given coverage criterion is achieved. This paper presents a formal framework in which evaluating an expression produces a tree structure, and where a coverage criterion is expressed as equivalence classes induced by a particular transformation over these trees. It then defines many well-known coverage criteria as particular cases of this framework. The paper describes an algorithm to generate test suites by a reduction through a graph problem; this algorithm works in the same way regardless of the criterion considered. An experimental evaluation of this technique shows that it produces test suites that are in many cases smaller than existing tools.